The relationship between pregnancy weight gain and birth weight of new born - Bilwal, Bharat Kumar; Garg, Apurva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Maternal weight gain is one of the most important independent predictors of infant birth weight. It is stated that under nutrition during pregnancy and low birth weight increase the risk for diabetes and cardiovascular disease in adulthood. Normal weight gain of pregnancy 11kg weight gain should be according to pre-pregnancy BMI. Patients with BMI > 25 should gain weight of 7kg patient with normal BMI should gain 11kg weights. Methods: This is a hospital based prospective study and was conducted in the Department of Obstetrics and Gynaecology, RNT Medical college Udaipur from November 2018 to March 2019 to find association between maternal weight gain and birth weight. Exclusion criteria included congenital malformations, multiple pregnancy, polyhydraminos, preeclampsia, diabetes, cardiovascular, kidney disease, RH negative pregnancy. Results were calculated by percentage. Results: excessive weight gain during pregnancy increases baby weight. Out of total 100 cases, 88 (88%) cases are Hindus and 12 (12%) cases are Muslims. Out of total 100 cases 72 cases (72%) belong to urban, 28 (28%) belong to Rural area. Out of 100 patients 32 patients gain weight less than 11kg among which 16 newborn have weight less than 2.5kg, 68 patients have weight gain more than 11kg and 67 have baby weight more than 2.5kg. Conclusions: Excessive maternal weight gain during pregnancy increases birth weight. In view of the apparent association between high birth weight and adult adiposity, an advantageous time to initiate obesity prevention efforts may be during pregnancy.